Conversations about sustainability (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. Starting a conversation about sustainability can be difficult. It's a complicated topic that sometimes requires people to understand some very technical ideas. Given that it also involves people's lifestyles, choices and values, it can be quite sensitive too. It's possible to make people aware of the need for more sustainable choices without it turning into a science lesson, a criticism of what they're doing now, or a political debate. You don't want to alienate them or cause them to become defensive. This is particularly important in the workplace, where you need to protect your working relationships. In this track, let's take a look at some strategies for starting the sustainability conversation at work and how you can inspire your colleagues to take action without creating tension. Learning Objectives Recognise why talking about sustainability needs to be approached with care Discover practical strategies for talking to colleagues about sustainability that will help influence their behaviour without damaging working relationships Establish how to have a productive discussion about sustainability with a manager.